Fluorogenic Trp(redBODIPY) cyclopeptide targeting keratin 1 for imaging of aggressive carcinomas - Subiros-Funosas, Ramon; Ho, Vivian Cheuk Lam; Barth, Nicole D; Mendive-Tapia, Lorena; Pappalardo, Morena; Barril, Xavier; Ma, Ruoyu; Zhang, Cheng-Bin; Qian, Bin-Zhi; Sintes, Miquel; Ghashghaei, Ouldouz; Lavilla, Rodolfo; et al. (Chemical science (Cambridge), 2020)
Keratin 1 (KRT1) is overexpressed in squamous carcinomas and associated with aggressive pathologies in breast cancer. Herein we report the design and preparation of the first Trp-based red fluorogenic amino acid, which is synthetically accessible in a few steps and displays excellent photophysical properties, and its application in a minimally-disruptive labelling strategy to prepare a new fluorogenic cyclopeptide for imaging of KRT1+ cells in whole intact tumour tissues. Trp(redBODIPY) is the first red-emitting Trp-based amino acid for the preparation of fluorogenic peptides with retention of target binding affinity.